How do you simplify frac{x^{2}+2x-80}{x^{2}-100}\cdot \frac{x^{2}-9x-10}{x^{2}-4x-32}?

1 Answer
Jun 14, 2017

"answer "(x+1)/(x+4)

Explanation:

(x^2+2x-80)/(x^2-100)*(x^2-9x-10)/(x^2-4x-32)
"Please remember the following mathematical identities."

x^2+2x-80=(x+10)(x-8)
x^2-100=x^2-10^2=(x-10)(x+10)
x^2-9x-10=(x-10)(x+1)
x^2-4x-32=(x-8)(x+4)
"let us write the equation again."
((x+10)(x-8))/((x-10)(x+10))*((x-10)(x+1))/((x-8)(x+4))

"let us simplify."

(cancel((x+10))cancel((x-8)))/(cancel((x+10))cancel((x-10)))*(cancel((x-10))(x+1))/(cancel((x-8))(x+4))

"we get;"
(x+1)/(x+4)